Virtual movement of relay nodes for two-tier wireless sensor networks in tunnels. (January 2017) - Bao, Yu; Zhao, Liang; Hu, Yuan; Tang, Chaogang; Aijuan, Zhang
In wireless sensor networks, node placement plays a significant role in terms of meeting design goals, such as cost effectiveness, connectivity, lifetime, and data latency. In tunnel environments, the energy consumption of sensor nodes and relay nodes is imbalanced because of the long and narrow shape of tunnels. In this article, to reduce the use of extra batteries and the number of forwarding times for a message, we propose a new approach to assist in the placement of relay nodes for two-tier wireless sensor networks in a tunnel environment. The approach proposed is based on the principle that working relay nodes can change approximately at the same time during network operation. It seems the relay nodes move to a new place when they are instead by dormant relay nodes. The approach provides a novel method that has been proved to find optimal places to deploy relay nodes in tunnel environment. Moreover, the approach balances the energy consumption of entire sensor nodes and prolongs the lifetime of entire networks significantly, which is shown in simulations.